Morphological and molecular characterization of mole crab (Genus: Emerita) in the Cilacap coastlines of Indonesia, with particular focus on genetic diversity of Emerita sp. nov. (Biodiversitas Journal of Biological Diversity, 2022)
Abstract.Bhagawati D, Nuryanto A, Winarni ET, Pulungsari AE. 2022. Morphological and molecular characterization of mole crab (Genus: Emerita) in the Cilacap coastlines of Indonesia, with particular focus on genetic diversity of Emerita sp. nov. Biodiversitas 23: 2395-2404. Previous studies reported Emerita emeritus is the only species of the Genus Emerita inhabiting the coastal ecosystem of the Cilacap District. A recent study reported the presence of suspected new Emerita species living on the Cilacap sandy beach but used a small number of specimens and no reports about genetic diversity. This study used more Emerita samples than the previous study. This study aimed to identify Emerita specimens based on the morphology and the cytochrome c oxidase 1 gene and analyzed the genetic diversity of Emerita sp. nov. Emerita samples were collected from three different beaches in Cilacap District, Central Java, Indonesia. Morphological identification placed the samples into two different morphotypes. Morphotype A was identified as Emerita emeritus. Morphotype B was determined as Emerita sp. nov. Molecular data support the placement of Emerita samples into Emerita emeritus, and Emeritasp. nov. Emeritasp. nov. has haplotype diversity of 0.857±0.057, indicating a high genetic diversity. Haplotype H2 was suggested as the most primitive one because other haplotypes radiated from it. This study concluded that two sympatric Emerita species inhabit Cilacap coastlines, and Emeritasp. nov. has high genetic diversity.